HIV diagnosis in a patient presenting with vasculitis. (February 2016) - Sharif, M; Hameed, S; Akin, I; Natarajan, U
A patient with digital ischaemia and gangrene was treated with iloprost and antiplatelets for two weeks. His vasculitic screen was negative except for a positive HIV test. His vasculitis improved three weeks after treatment with antiretroviral medications. Though vasculitis is well known to be associated with HIV infection, very few cases of HIV present as vasculitis.